The relationship between transposable elements and ecological niches in the Greater Cape Floristic Region: A study on the genus Pteronia (Asteraceae) - Chumová, Zuzana; Belyayev, Alexander; Mandáková, Terezie; Zeisek, Vojtěch; Hodková, Eva; Šemberová, Kristýna; Euston-Brown, Douglas; Trávníček, Pavel (Frontiers in Plant Science, 2022)
Non-coding repetitive DNA (repeatome) is an active part of the nuclear genome, involved in its structure, evolution and function. It is dominated by transposable elements (TEs) and satellite DNA and is prone to the most rapid changes over time. The TEs activity presumably causes the global genome reorganization and may play an adaptive or regulatory role in response to environmental challenges. This assumption is applied here for the first time to plants from the Cape Floristic hotspot to determine whether changes in repetitive DNA are related to responses to a harsh, but extremely species-rich environment. The genus Pteronia (Asteraceae) serves as a suitable model group because it shows considerable variation in genome size at the diploid level and has high and nearly equal levels of endemism in the two main Cape biomes, Fynbos and Succulent Karoo. First, we constructed a phylogeny based on multiple low-copy genes that served as a phylogenetic framework for detecting quantitative and qualitative changes in the repeatome. Second, we performed a comparative analysis of the environments of two groups of Pteronia differing in their TEs bursts. Our results suggest that the environmental transition from the Succulent Karoo to the Fynbos is accompanied by TEs burst, which is likely also driving phylogenetic divergence. We thus hypothesize that analysis of rapidly evolving repeatome could serve as an important proxy for determining the molecular basis of lineage divergence in rapidly radiating groups.